An Empirical Analysis of Consumer Purchase Behavior Towards Organic Food Products in Selected Areas of Thanjavur - EDISON, MR.L. PAUL; DR.R.P. RAMESH, (The journal of contemporary issues in business and government, 2021)
The primary goal of this study is to identify four main determinants affecting buying intentions for organically grown foods based on existing studies, with the goal of better understanding the relationship between these key determinants and buyers in the selected cities of Thanjavur. With a final survey of 60 respondents, four hypotheses were formed and evaluated. Market buying intentions were significantly influenced by the determinants of food quality, convenience, and price, as well as purchase behaviour, according to multiple regression study. Supporting small producers, on the other hand, had a detrimental effect. Furthermore, there was no connection between attitude and purchasing purpose. In order to quickly expand this critical segment, the Indian government, strategists, producers, and marketing experts must concentrate more emphasis on the benefits of organically grown foods, according to the findings.